AN ANALYSIS OF GRAMMATICAL COHESIVE DEVICES IN STUDENTS’WRITING RECOUNT TEXT - Shela Rizqi Wiraningsih (Journal of English Education Program (JEEP), 2014)
This study investigates grammatical cohesive devices in recount texts written by the tenth grade students of a senior high school in Ciamis. This study was aimed to find out types of grammatical cohesive devices are found in students’ writing recount text and to find out types of grammatical cohesive devices are mostly found in students’ writing recount text. This study was a qualitative study with descriptive method in which the writer gave description and explanation about grammatical cohesive devices found in the students’ recount text.  The data were analyzed through the theory of cohesion by Halliday and Hasan (1976). The 21 students at tenth grade of a senior high school in Ciamis were chosen purposively as the sample because they have learned recount text. The result showed that the types of grammatical cohesive devices found in the students’ recount text were in the form of reference, ellipsis and conjunction. However, there was no substitution found in students’ recount text. As the percentage of reference items is 76%, ellipsis is 2% and conjunction is 22%. It can be concluded that reference becomes the first dominant, conjunction as the second dominant, and ellipsis as the last dominant. This study can give pedagogical implication for English language teaching, especially for, reading and writing class. Key words: Cohesion, cohesive devices, grammatical cohesive devices, recount text